Kesiapan berwirausaha pada siswa SMK kompetensi keahlian jasa boga - Anggri Sekar Sari (Jurnal Pendidikan Vokasi, 2012)
Tujuan penelitian untuk mengungkapkan pengaruh peranan orangtua, ketrampilan pengelolaan UJB, dan self-efficacy terhadap kesiapan berwirausaha. Penelitian menggunakan pendekatan ex post facto. Populasi adalah siswa SMK Kompetensi Keahlian Jasa Boga di DIY. Sampel sebanyak 198 responden ditentukan menggunakan teknik proportional random sampling. Data dikumpulkan dengan instrumen angket dan tes. Analisis data menggunakan statistik deskriptif dan regresi linier berganda. Penelitian menunjukkan kesiapan berwirausaha relatif sedang (30,8%). Uji hipotesis menemukan bahwa variabel peranan orangtua berpengaruh positif dan signifikan terhadap kesiapan berwirausaha sebesar 0,374 (sig 0,000). Begitu pula ketrampilan pengelolaan UJB sebesar 0,256 (sig 0,000) dan self-efficacy sebesar 0,191 (sig 0,007) berpengaruh positif dan signifikan terhadap kesiapan berwirausaha. Terdapat pengaruh secara bersama-sama antara peranan orangtua, ketrampilan pengelolaan UJB, dan self efficacy sebesar 55% terhadap kesiapan berwirausaha. THE ENTREPRENEURIAL READINESS OF THE STUDENTS OF THE FOOD & BEVERAGE SKILL COMPETENCY IN PUBLIC VOCATIONAL HIGH SCHOOLSAbstractThe purposes of this research are to reveal the effect of parents` roles, vocational skills in the Food & Beverage Business Management, and self-efficacy on the entrepreneurial readiness. This study uses the ex post facto approach. The population is the students of the food & beverage skill competency in public vocational high schools in Yogyakarta Spesial Territory. A sample of 198 respondents is established using the proportional random sampling technique. The data are collected using questionnaires and a test. The data are analyzed using descriptive statistics and using multiple linear regression. The results show that almost half (30.8) of students have a low entrepreneurial readiness. The hypothesis testing shows that the parents` roles have a positive and significant effect on the entrepreneurial readiness as much as 0.374 (sig 0.000). Similarly, vocational skills in the Food & Beverage Business Management and self-efficacy have significant and positive effects on the entrepreneurial readiness as much as 0.256 (sig 0.000) and as much as 0.191 (sig 0.007) respectively The of parents` roles, vocational skills in the Food & Beverage Business Management, and self-efficacy collectively have the effect of 55 percent on the entrepreneurial readiness.